Preliminary investigation on the tensile properties of FDM printed PLA/copper composite - Rajan, K.; Kottasamy, A.; Mogan, J.; Sandanamsamy, L.; M., Samykano; K., Kadirgama; Wan Sharuzi, Wan Harun (Springer, 2023)
Recently, the rapid manufacturing of custom polymer-based composite components has been revolutionized by the Fused deposition modeling (FDM) process. Understanding the fundamental mechanical behaviours of these FDM-printed components is essential for engineering applications. FDM has been highly used inadditive manufacturing (AM) due to its ability to process complex parts with the lowest cost and accurate dimensions. The materials used are thermoplastic polymers, which are in the form of a filament. The aim of this study is to create testing specimens with varying infill percentages (25%, 50%, and 75%) and infill patterns (rectilinear, honeycomb, grid, concentric, and triangle) using the FDM technique on Polylactic acid (PLA) and PLA/Copper. The specimen is printed in accordance with the ASTM standard for tensile testing, which is ASTM D638. Following that, the mechanical properties of copper are assessed using tensile testing. The results demonstrate that the infill pattern for a triangle PLA/Copper specimen and concentric PLA specimen for 75% infill percentage produced the best performance in tensile strength; meanwhile, the grid copper pattern has the weakest properties among all the patterns. This research will be helpful to enhance the mechanical properties of the products in the electronics applications.